THE DEVELOPMENT OF STUDENT CARE AND SUPPORT SYSTEM USING PARTICIPATORY MANAGEMENT OF SCHOOLS UNDER CHAIYAPHUM PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Srisamer, Panida; Namwan, Tharinthorn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The purposes of this research were 1) To study the current conditions. The desirable conditions and needs of the Student Care and Support System using participatory management of schools under Chaiyaphum Primary Educational Service Area Office 2. and 2) To develop guidelines for the implementation of student care and support systems by using participatory management of schools under the Chaiyaphum Primary Educational Service Area Office 2. The research was divided into two phases. (1) To study the current conditions. Desirable conditions for the operation of the Student Care and Support System using participatory management of schools under Chaiyaphum Primary Educational Service Area Office 2. by using a questionnaire to collect data from a sample group of 354 administrators, teachers and Education Committees. Then prioritize the necessary needs of the operation. (2) Guidelines for the implementation of the Student Care and Support System using participatory management of schools under Chaiyaphum Primary Educational Service Area Office 2, by studying and synthesizing the current and desirable conditions used to develop guidelines for the implementation of the Student Care and Support System from administrators and teachers by in-depth interviews with 3 best practice schools. Draft as a guideline for the development of a student care system and assess the guidelines by 5 experts. The research instruments were questionnaires, interviews and assessments. The statistics used for data analysis were percentage, mean and standard deviation. The results of the research were as follows: 1. Current conditions, desirable conditions, and prioritization of the needs of the Student Care and Support System using participatory management of schools under Chaiyaphum Primary Educational Service Area Office 2. Overall current condition was at a high level. The highest mean is promoting students. Overall desirable condition was at the highest level. The highest mean is prevention and problem solving. The order of needs, the aspect with the most need is the forwarding. 2. Guidelines for the operation of the Student Care and Support System using participatory management of schools under Chaiyaphum Primary Educational Service Area Office 2, consists of 5 elements, 25 approaches, namely 1) knowing students individually, 5 approaches, 2) student screening, 5 approaches, 3) student support, 5 approaches, 4) prevention and problem solving, 5 approaches, and 5) Forwarding 5 approaches. The results of assessing the feasibility and feasibility of the development of the Student Care and Support System using participatory management of schools under Chaiyaphum Primary Educational Service Area Office 2. found that: The guidelines are appropriate and there is at the most level of overall possibilities. When considering each item, it was found that all approaches were appropriate. At the highest level, the same for all items. The aspect that is most appropriate is the aspect of promoting students. The feasibility of the overall approach was at the highest level. When considering each item, it was found that it was most likely the same for all items. The most likely aspect is student screening.